Answer:
- 2(x + 2) + 2 = 2(x + 3) + 1
- 2x + 3(x + 5) = 5(x – 3)
- 5(x + 4) – x = 4(x + 5) – 1
Explanation:
It can be easier to see the answer if you subtract the right side of the equation from both sides, then simplify.
1. 2(x + 2) + 2 = 2(x + 3) + 1
2(x + 2) + 2 - (2(x + 3) + 1) = 0
2x +4 +2 -2x -6 -1 = 0
-1 = 0 . . . . no solution
__
2. 2x + 3(x + 5) = 5(x – 3)
2x + 3(x + 5) - 5(x – 3) = 0
2x +3x +15 -5x +15 = 0
30 = 0 . . . . no solution
__
3. 4(x + 3) = x + 12
4(x + 3) - (x + 12) = 0
4x +12 -x -12 = 0
3x = 0 . . . . one solution, x=0
__
4. 4 – (2x + 5) = (–4x – 2)
4 – (2x + 5) - (–4x – 2) = 0
4 -2x -5 +4x +2 = 0
2x +1 = 0 . . . . one solution, x=-1/2
__
5. 5(x + 4) – x = 4(x + 5) – 1
5(x + 4) – x - (4(x + 5) – 1) = 0
5x +20 -x -4x -20 +1 = 0
1 = 0 . . . . no solution